Preparation and Characterization of Natural Fragrant Microcapsules (Journal of Fiber Bioengineering and Informatics, 2018)
Natural fragrant microcapsules with ethyl cellulose (EC) as a shell and lavender oil as acore were prepared by emulsify-solvent diffusion method. The characters, including particle size,encapsulation efficiency and oil loading capacity, were tested and analyzed by using orthogonaldesign. The processing parameters of the ratio of an oil phase to water phase, the ratio of core materialto shell material, concentration of PVA and stirring speed were evaluated. The morphology andstructure features of microcapsules were studied by SEM, FT-IR and etc. The results showed that themicrocapsules were in sphere shape and most of the particle size was about 1